LONG-TERM INFLUENCE OF INTEGRATED NUTRIENT MANAGEMENT ON SOIL FERTILITY CHANGES AND TOTAL UPTAKE UNDER RICE-RICE CROPPING SYSTEM - P.V. GEETHA SIREESHA*, G. PADMAJA and P.C. RAO, (The Journal of Research ANGRAU, 2019)
A long-term field experiment was initiated during Kharif, 1989 to study the effect of the combination of organicand inorganic fertilizers on yield, fertility status and uptake pattern of nutrients in rice-rice cropping system. Theresults pertaining to 2013-14 were presented in this article. The pH values of 1:2.5 soil-water suspensions rangedfrom 5.3 to 5.9 after harvest of Kharif and Rabi rice, indicating moderately acidic to slightly acidic in reaction.ECdecreased slightly from the initial (1.09 dSm-1) and ranged from 0.78 dSm-1 to 0.95 dSm-1 indicating non-salinenature. The highest organic carbon content (1.70% and 1.88%, respectively) was noticed in the treatment receiving50% RD of NPK + 50% N through FYM in Kharif and Rabi. Application of FYM along with 100% NPK producedsignificantly higher yields under both Kharif (7402 kg ha-1) and Rabi (7267 kg ha-1) than the application of 100% NPK(7075 and 7150 kg ha-1) and FYM (5777 kg ha-1 and 4533 kg ha-1) alone treated plots. Nutrient uptake (kg ha-1) of strawunder Kharifindicated that nitrogen, phosphorus and potassium uptake was higher in T4 with uptake values of 93.5kg ha-1, 44.9 kg ha-1 and 184.2 kg ha-1, respectively. Application of 100% RD of NPK + FYM @ 5 t ha-1 was effective inincreasing grain and straw yield of rice.